2017
DOI: 10.20472/ss2017.6.2.004
|View full text |Cite
|
Sign up to set email alerts
|

A Pattern Analysis Application: Time Series Traces of the Effect of Kamran Khavarani’s Paintings on Viewers’ Mood

Abstract: Abstract:We

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…Mozayeni and Amirmostofian (2016) showed that viewers of Abstract Romanticism paintings, irrespective of their gender and age and their initial state of mood, reported an increase in positive mood. Mozayeni, et al (2017), conducted a pattern analysis of mood reports of individuals who visited three galleries, one of which was the Abstract Romanticism gallery (Khavarani's Gallery). Before and after moods were reported by viewers for each gallery they visited.…”
Section: Reduced Distress Leads To Positive Health Outcomesmentioning
confidence: 99%
See 3 more Smart Citations
“…Mozayeni and Amirmostofian (2016) showed that viewers of Abstract Romanticism paintings, irrespective of their gender and age and their initial state of mood, reported an increase in positive mood. Mozayeni, et al (2017), conducted a pattern analysis of mood reports of individuals who visited three galleries, one of which was the Abstract Romanticism gallery (Khavarani's Gallery). Before and after moods were reported by viewers for each gallery they visited.…”
Section: Reduced Distress Leads To Positive Health Outcomesmentioning
confidence: 99%
“…In addition, there was no discernible effect of order, gender, or age on mood scores. Based on previous research examining the uplifting power of the Abstract Romanticism (AR) genre of painting Mozayeni, et al, 2017), we considered their use in hospitals. In the present study, we conducted a Cost-Benefit Analysis to predict the potential benefits of using the Abstract Romanticism genre of painting to reduce the length of hospital stays and thus associated costs.…”
Section: Reduced Distress Leads To Positive Health Outcomesmentioning
confidence: 99%
See 2 more Smart Citations